Inactivation of Bacillus anthracis by Gamma irradiation - Natalia, N.; Priadi, A.; Irawati, Z. (Indonesian Animal Sciences Society, 2009)
The use of Bacillus anthracis as a biological weapon heighlightened awareness of the need for validated methods for the inactivation of B. anthracis spores. Ionizing radiation is capable of causing a variety of chemical changes and biological effects on bacteria which can be due both to direct interactions with critical cell components and to indirect actions on bacteria by molecular entities formed as a result of radiolysis of other molecules in the bacterial cell. This study determined the gamma irradiation dose for inactivating B. anthracis spores and its biological effects on the bacterial characteristics. Gamma irradiation was conducted at the IRKA irradiator at the National Nuclear Energy Agency, Jakarta and cobalt-60 was used as the source of ionizing radiation (capacity of ca. 134,044 Kci). Freeze dried culture of B. anthracis in glass ampoules was irradiated usingÂ Â variable doses of 30, 20 and 10 KGy. Viability, biochemical and protease enzyme characteristics of B. anthracis were evaluated before and after irradiation.Â The ability of B. anthracis to degrade gelatin, haemoglobin and bovine immunoglobulin G was also tested. The results showed that ionizing radiationÂ was able to inactivate or kill 11,05 x 108 cfu B. anthracis by 95.37%, 99.58% and 99.99 at respective doses of 10, 20 and 30 KGy. Bacterial spores appear to be less susceptible to irradiation than the vegetative cells, because of their specific structure. The survive spores irradiated at 30kGy shows some biochemical characteristic changes. The survivors failed to degrade methyl ï-D-glucopyranoside and arbutine. The ability of B. anthracis protease to degrade gelatin, haemoglobin and bovine immunoglobulin G was not affected by irradiation. These findings showed that a gamma irradiation at 30 KGy effectively inactivates B. anthracis spores without changing the protease activities. Key words: Gamma Irradiation, B. anthracis Characters, Protease